مذہبی تصنیفات اور اصلاح ِ اخلاق میں جامعہ دار العلوم حقانیہ اکوڑہ خٹک کا کردار:مفتی محمد فرید اور ان کے منتخب خلفا و مریدین کی خدمات کا مطالعہ : Role of Jāmia Ḥaqqānia Akora Khattak in Religious writings and Moral reform: A Study of the Services of Muftī Muhammad Farīd and some of his Disciples and Followers - Muhammd Ayaz; Dr. Badshah Rehman; Dr. Ataurrahman (Al-Qamar, 2019)
This article studies the services of the ʻUlamāʻ of Dār al-ʻUlūm Jāmia Ḥaqqānia Akora Khattak in the field of religious writings and moral reform. It focuses in this regard on the services of a prominent scholar of the Jāmia Muftī Muhammad Farīd and his disciples and followers Hāfiz Hussain Ahmad Siddīquī, Muftī Muhammad Wahhāb Manglorī, Mawālānā Muhammad Amīn Dost, Mawālānā Abdullah Naqshbandī and Mawālānā Muhammad Āyāz Kāngra. It finds that the services of these scholars in the fields referred are unforgettable. There is a need to get benefit of these scholars and their services to rectify the flaws in the society.